Relationships between physical frailty and cognitive decline over 8 years: A longitudinal study among community-dwelling older Chinese immigrants - Fengyan Tang; Qingqing Yin; Wendi Da; Guoping Jin; Yanping Jiang (The Journal of Nutrition, Health and Aging)
Objectives: To examine patterns of physical frailty changes, their sociocultural correlates, and associations with initial cognitive functioning and cognitive decline over an eight-year observation period among community-dwelling older Chinese immigrants. Design: An 8-year follow-up longitudinal study. Setting and participants: 2,835 community-dwelling adults aged 60 and above living in Chicago, who self-identified as Chinese, with a mean age of 72.5 years at baseline. Measurements: Frailty was assessed using five indicators across the five waves, and patterns of change were identified through repeated measures latent class analysis (RMLCA). Cognitive functioning was assessed using the Chinese Mini-Mental State Examination (C-MMSE). The associations between frailty patterns and cognitive change trajectories were evaluated using latent growth curve modeling (LGCM), adjusted for sociodemographic, health, and immigration covariates. Results: Four distinct frailty patterns were identified: least frail (53%), decreased frailty (21%), increased frailty (15%), and constantly frail (11%), with differential sociodemographic and immigration profiles. Compared to the least frail class, respondents in the increased frailty class (intercept: B = −0.108, p < .05; slope: B = −0.073, p < .001) and the constantly frail class (intercept: B = −0.150, p < .01; slope: B = −0.043, p < .001) showed poorer initial cognitive functioning and faster rates of cognitive decline after controlling for covariates. No significant differences in cognitive outcomes were observed between the least frail and the decreased frailty classes. Compared to Cantonese speakers, Mandarin speakers experienced a slower rate of cognitive decline (B = 0.033, p < .001). Conclusions: These findings demonstrate that physical frailty is associated with cognitive decline, particularly among older Chinese immigrants who remain constantly frail or experience increasing frailty over time. Clinical interventions should prioritize addressing both physical frailty and cognitive decline, with special attention to vulnerable subgroups within this population.